From performance to exhaustion:: Burnout and precarization in the Post-Digital Creator Economy (Intercom - Brazilian Journal of Communication Sciences, 2026)
The present study aims to understand how Burnout Syndrome, manifested asexhaustion and occupational stress, impacts the Creator Economy and affectsnew generations. The research deepens the analysis of the performance crisisamidst intense technological changes in work, which affect the subjectivityand the commodified identity construction of young creators. Burnout isarticulated as a symptom of digital techno-neoliberal capitalism, establishinga dialogue with Brazilian structural issues, such as the precariousness ofPejotização and the logic of the Gig Economy. The methodology consists ofan exploratory bibliographic review that supports the theoretical framework.The focus resides on the contribution to the field of Communication, throughthe examination of market transformations, algorithmic management, andthe incessant pursuit of professional relevance.
Keywords: Burnout; creator economy; post-digital era employment; media consumption and production